Modulation of β1-integrins on hemopoietic progenitor cells after allergen challenge in asthmatic subjects - Catalli, Adriana E.; Thomson, Jennifer V.; Babirad, Irene M.; Duong, MyLinh; Doyle, Tracey M.; Howie, Karen J.; Newbold, Paul; Craggs, Richard I.; Foster, Martyn; Gauvreau, Gail M.; O'Byrne, Paul M.; Sehmi, Roma (Journal of allergy and clinical immunology, 2008)
Mobilization of hemopoietic progenitor cells from the bone marrow (BM) is a feature of inflammatory asthmatic responses. Understanding the mechanisms regulating progenitor cell mobilization and trafficking to the peripheral circulation might be important for the development of effective asthma therapies. We investigated the role of adhesion molecules in the mobilization of hemopoietic progenitor cells from the BM during an allergen-induced asthmatic response. BM and peripheral blood samples were obtained from dual-responders with mild asthma before and at several time points after allergen challenge. Fluctuations in expression and adhesive properties of β1- and β2-integrins on CD34+CD45+ progenitor cells were assessed by using flow cytometry and adhesion to protein-coated wells, respectively. On BM-derived CD34+CD45+ cells, expression of very late antigen (VLA) 4, but not VLA-5 or Mac-1, decreased significantly 24 hours after allergen challenge and had begun to recover by 48 hours after challenge. In peripheral blood allergen challenge induced a significant decrease in VLA-4 levels after 6 hours, which had not recovered by 96 hours after challenge. Similarly, VLA-5 expression decreased, most prominently at 72 to 96 hours after allergen challenge. In contrast, Mac-1 levels did not change. Chemokine-stimulated adhesion of BM-derived CD34+CD45+ cells to fibronectin was significantly attenuated 24 hours after challenge. Furthermore, adhesion to fibronectin and vascular cell adhesion molecule 1 was greatly reduced by anti-VLA-4 or anti-VLA-5 antibodies. Preferential downregulation of β1-integrin expression on progenitor cells can reduce the tethering forces to BM components, thus facilitating their egress to the peripheral circulation during an allergic inflammatory response.